PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN PERILAKU BELAJAR TERHADAP PEMAHAMAN AKUNTANSI MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SAM RATULANGI MANADO - Parauba, Inriawati (Universitas Sam Ratulangi, 2014)
Globalization is definitely demanding of the human resources that have the skills in every fields of works so that they can be compete in the business world. In order to deal with this globalization, it needs the skills that absolutely to be reached by continuous study process, which one of them is the accounting skill that’s very needed in the economy nowadays. In order to face this competition, education world especially accounting demanded to produce the high quality output or the graduates and ready to compete in the jobs world. This research aimed to prove the influence of intelligence quotient, emotional quotient, spiritual quotient, and study behavior towards understanding of accounting of the student of Economic and Business Faculty, Sam Ratulangi University. The analysis method is linier double regression. The result gives the conclusion that is the intelligence quotient, emotional quotient, spiritual quotient, and the study behavior simultaneously have influence towards understanding of accounting of the students of Economic and Bussines Faculty, Sam Ratulangi University, while partially, intelligence quotient, emotional quotient, spiritual quotient, and study behavior significantly have not the influence towards understanding of accounting of the student of Economic and Bussines Faculty, Sam Ratulangi University Manado.